Changes in Body Composition of Pulmonary Tuberculosis Patients Undergoing Intensive Phase Treatment - Jose Sepputro Sutrisno; Suryadinata, Rivan Virlando; Dwi Martha Nur Aditya (Indonesian Journal of Human Nutrition, 2024)
Pulmonary tuberculosis (TB) cases in Indonesia continue to increase every year, and malnutrition is identified as one of the causes in increasing susceptibility to disease transmission. Decreased nutritional intake can be assessed through changes in body composition. The initiation of intensive phase tuberculosis therapy is crucial for reducing bacterial growth and preventing recurrence, which can help improve food intake in TB patients. This study aims to determine changes in body composition in tuberculosis patients undergoing intensive phase treatment. This observational cohort study was conducted in Nganjuk Regency, East Java, from December 2023 to July 2024. The research sample consisted of 35 newly diagnosed tuberculosis patients undergoing intensive treatment. The parameters in this study, namely the percentage of fat mass, subcutaneous fat, skeletal mass, and visceral fat levels, were measured before and after two months of intensive treatment. The research results showed a significant increase in fat mass and visceral fat (p≤0.05). Meanwhile, the body mass index and fat-free mass showed an increase but were not significant (p>0.05). Overall, this study showed an improvement in body composition in tuberculosis patients after undergoing intensive phase treatment.